1999
DOI: 10.2202/1949-6605.1092
|View full text |Cite
|
Sign up to set email alerts
|

The Freshman Year Experience: Student Rotation and Student Success

Abstract: This ex post facto controlled investigation was conducted +om 1993 to 1996 at a medium sized, regional, predominantly mite, public, four-year university in the Midwest to determine the~elationship between participation in the institution 'sfreshman year e~wience couyse and student~etention and success. Students who participated in the course were found to continue thei~enrollment to thefall te~m of their second year at a higher rate, complete moye of the first academic year, earn higho cumulative Fade point av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A few studies, such as those by Hendel (2001), Hendel (2007), and Erickson and Stone (2012) found that first-year seminars had no direct impact on student retention in the second year. However, most research has reported a positive impact on student retention and performance (Fidler,1991;Fidler and Moore,1996;Strake et al, 2001;Lang, 2007;Jamelsk, 2009;Sidle and McReynolds, 1999). Recent studies that have explored the impact on student GPA and retention are Winnie (2012), Berry (2014), Vaughan et al (2014), and Newman (2016).…”
Section: General Attitudes Toward Higher Educationmentioning
confidence: 99%
“…A few studies, such as those by Hendel (2001), Hendel (2007), and Erickson and Stone (2012) found that first-year seminars had no direct impact on student retention in the second year. However, most research has reported a positive impact on student retention and performance (Fidler,1991;Fidler and Moore,1996;Strake et al, 2001;Lang, 2007;Jamelsk, 2009;Sidle and McReynolds, 1999). Recent studies that have explored the impact on student GPA and retention are Winnie (2012), Berry (2014), Vaughan et al (2014), and Newman (2016).…”
Section: General Attitudes Toward Higher Educationmentioning
confidence: 99%